2010
DOI: 10.1105/tpc.110.075507
|View full text |Cite
|
Sign up to set email alerts
|

The Type IIArabidopsisFormin14 Interacts with Microtubules and Microfilaments to Regulate Cell Division  

Abstract: Formins have long been known to regulate microfilaments but have also recently been shown to associate with microtubules. In this study, Arabidopsis thaliana FORMIN14 (AFH14), a type II formin, was found to regulate both microtubule and microfilament arrays. AFH14 expressed in BY-2 cells was shown to decorate preprophase bands, spindles, and phragmoplasts and to induce coalignment of microtubules with microfilaments. These effects perturbed the process of cell division. Localization of AFH14 to microtubule-bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
148
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 117 publications
(161 citation statements)
references
References 93 publications
12
148
1
Order By: Relevance
“…In vivo observations have long suggested that formins also regulate MT organization and dynamics (Kikyo et al, 1999;Lee et al, 1999;Chang, 2000;Ishizaki et al, 2001;Kato et al, 2001;Leader et al, 2002;Deeks et al, 2010;Li et al, 2010). Expression of constitutively active mDia constructs results in co-alignment of MTs and actin fibers , promotes MT targeting to the cell periphery (Yamana et al, 2006;Goulimari et al, 2008;Zaoui et al, 2010) and stabilizes MTs (Palazzo et al, 2001;Wen et al, 2004;Eng et al, 2006;Bartolini et al, 2008).…”
Section: Regulation Of Microtubule Dynamicsmentioning
confidence: 99%
“…In vivo observations have long suggested that formins also regulate MT organization and dynamics (Kikyo et al, 1999;Lee et al, 1999;Chang, 2000;Ishizaki et al, 2001;Kato et al, 2001;Leader et al, 2002;Deeks et al, 2010;Li et al, 2010). Expression of constitutively active mDia constructs results in co-alignment of MTs and actin fibers , promotes MT targeting to the cell periphery (Yamana et al, 2006;Goulimari et al, 2008;Zaoui et al, 2010) and stabilizes MTs (Palazzo et al, 2001;Wen et al, 2004;Eng et al, 2006;Bartolini et al, 2008).…”
Section: Regulation Of Microtubule Dynamicsmentioning
confidence: 99%
“…It was shown very recently that several Arabidopsis formins interact directly with microtubules (Deeks et al, 2010;Li et al, 2010), which prompted us to determine whether FH5 interacts with microtubules. To test this, we first performed microtubule cosedimentation assays.…”
Section: Fh5 Binds To and Bundles Microtubules In Vitro But Loss Of mentioning
confidence: 99%
“…Recent results from the moss Physcomitrella patens demonstrated that class II formins could elongate actin filaments at an amazingly rapid rate and are essential for polar cell expansion (Vidali et al, 2009). Most recently, a class II formin, AFH14, was reported to bind both microtubules and microfilaments and was shown to play important roles in cell division and microspore formation in Arabidopsis (Li et al, 2010). However, it remains a major challenge to explore the physiological functions of each formin protein in plants, particularly in the model cereal rice, for which no single formin has been functionally characterized.…”
Section: Introductionmentioning
confidence: 99%
“…Actin filaments are highly dynamic, undergoing rapid reorganization and turnover regulated by actin binding proteins such as ADF/cofilin, villin, profilin, fimbrin, and capping protein (Wasteneys and Galway, 2003;Hussey et al, 2006;Staiger and Blanchoin, 2006;Higaki et al, 2007;Thomas et al, 2009;Li et al, 2010;Su et al, 2012;Qu et al, 2013;Wang et al, 2015). ADF/cofilin proteins function as key regulators of actin filament dynamics and reorganization through binding to both globular and filamentous actin.…”
Section: Introductionmentioning
confidence: 99%